2002
DOI: 10.1103/physrevb.66.125315
|View full text |Cite
|
Sign up to set email alerts
|

Interference in interacting quantum dots with spin

Abstract: We study spectral and transport properties of interacting quantum dots with spin. Two particular model systems are investigated: Lateral multilevel and two parallel quantum dots. In both cases different paths through the system can give rise to interference. We demonstrate that this strengthens the multilevel Kondo effect for which a simple two-stage mechanism is proposed. In parallel dots we show under which conditions the peak of an interference-induced orbital Kondo effect can be split.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 42 publications
0
106
0
Order By: Relevance
“…1 [15,16,17,18,19,20,21,22,51]. In the following discussions, the intra-dot Coulomb interaction is assumed to be sufficiently large, so that double occupancy on each QD is forbidden.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 [15,16,17,18,19,20,21,22,51]. In the following discussions, the intra-dot Coulomb interaction is assumed to be sufficiently large, so that double occupancy on each QD is forbidden.…”
Section: Model and Methodsmentioning
confidence: 99%
“…There have been a number of theoretical works on DQD systems in this context. For example, it was pointed out that the DQD system shows the dramatic suppression of the Kondo-assisted transport due to the interference when the DQD is arranged in the parallel geometry [15,16,17,18,19,20,21,22], whereas such interference effects do not appear in the serial DQD [16,23,24,25,26,27,28,29,30]. More recently, slightly different DQD systems with the parallel geometry, where the two dots are connected via the exchange coupling [19] or the tunneling [20,21], have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…These effects on the average electric current and level population [19][20][21][22][23][24] do not require a magnetic field as in double quantum dot Aharonov-Bohm interferometers. [25][26][27][28][29][30] A recent study of interference effects on the electron transfer statistics showed that they can induce super-Poisson shot noise in the Coulomb blockade regime and the high bias limit. 18 Using the terminology of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…the unitarity limit for the zerobias conductance at low temperatures [5]. There is naturally considerable interest in coupled quantum dots at present, notably double dot (DQD) systems which are under active investigation both theoretically [6][7][8][9][10][11][12][13][14][15][16][17][18] and experimentally [19][20][21][22][23][24][25][26][27]. In addition to their possible utility in mesoscopic devices, circuitry and information processing, such systems offer the prospect of novel strongly correlated electron states, reflecting the inherent relevance of both spin and orbital degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%